Impact of childhood trauma on risk of relapse requiring psychiatric hospital admission for psychosis. (August 2016) - Petros, N.; Foglia, E.; Klamerus, E.; Beards, S.; Murray, R. M.; Bhattacharyya, S.
Summary: Relapse in psychosis typically necessitates admission to hospital placing a significant financial burden on the health service. Exposure to childhood trauma is associated with an increased risk of psychosis, however, the extent to which this influences relapse is unclear. This report summarises current research investigating the influence of childhood trauma on relapse requiring psychiatric hospital admission for psychosis. Seven studies were included; two revealed a positive association between childhood trauma and relapse admission, two studies found a negative relationship and three found no significant difference. Inconsistent current evidence suggests a need for further research in this area.